Modeling and predicting optimal treatment scheduling between the antiangiogenic drug sunitinib and irinotecan in preclinical settings. (11th December 2015) - Wilson, S; Tod, M; Ouerdani, A; Emde, A; Yarden, Y; Adda Berkane, A; Kassour, S; Wei, MX; Freyer, G; You, B; Grenier, E; Ribba, B
Abstract : We present a system of nonlinear ordinary differential equations used to quantify the complex dynamics of the interactions between tumor growth, vasculature generation, and antiangiogenic treatment. The primary dataset consists of longitudinal tumor size measurements (1, 371 total observations) in 105 colorectal tumor‐bearing mice. Mice received single or combination administration of sunitinib, an antiangiogenic agent, and/or irinotecan, a cytotoxic agent. Depending on the dataset, parameter estimation was performed either using a mixed‐effect approach or by nonlinear least squares. Through a log‐likelihood ratio test, we conclude that there is a potential synergistic interaction between sunitinib when administered in combination with irinotecan in preclinical settings. Model simulations were then compared to data from a follow‐up preclinical experiment. We conclude that the model has predictive value in identifying the therapeutic window in which the timing between the administrations of these two drugs is most effective.